2009
DOI: 10.2353/ajpath.2009.081019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glutathione S-Transferase Pi as a Protein Involved in Parkinson Disease Progression

Abstract: Parkinson disease (PD) typically affects the cortical regions during the later stages of disease, with neuronal loss, gliosis, and formation of diffuse cortical Lewy bodies in a significant portion of patients with dementia. To identify novel proteins involved in PD progression, we prepared synaptosomal fractions from the frontal cortices of pathologically verified PD patients at different stages along with age-matched controls. Protein expression profiles were compared using a robust quantitative proteomic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 72 publications
(92 reference statements)
2
71
0
Order By: Relevance
“…Interestingly, GSTpi is enriched in the striatum and dopamine neuron-containing regions of the ventral mesencephalon (Castro-Caldas et al, 2009). Accordingly, GSTP1P2-KO mice show an enhanced sensitivity to MPTPinduced dopamine depletion (Smeyne et al, 2007), and overexpression of three allelic GSTpi variants provides protection against rotenone-induced dopaminergic cell loss (Shi et al, 2009). In addition, human polymorphisms in GSTpi have been shown to increase susceptibility to Parkinson's disease (Vilar et al, 2007).…”
Section: Cocaine Changes Gstpi Expressionmentioning
confidence: 99%
“…Interestingly, GSTpi is enriched in the striatum and dopamine neuron-containing regions of the ventral mesencephalon (Castro-Caldas et al, 2009). Accordingly, GSTP1P2-KO mice show an enhanced sensitivity to MPTPinduced dopamine depletion (Smeyne et al, 2007), and overexpression of three allelic GSTpi variants provides protection against rotenone-induced dopaminergic cell loss (Shi et al, 2009). In addition, human polymorphisms in GSTpi have been shown to increase susceptibility to Parkinson's disease (Vilar et al, 2007).…”
Section: Cocaine Changes Gstpi Expressionmentioning
confidence: 99%
“…The V/V homozygote did not show any association with PD, which was also reported by other authors 8,14 . The presence of the Val105 (V) allelic variant of GSTP1 is associated with the decrease of the enzyme activity, which would favor dopaminergic neurons degeneration in PD 4,15 . However, in this study, the wild genotype (I/I) presented association with familial PD.…”
Section: Discussionmentioning
confidence: 99%
“…Associations can be observed between GSTP1*B and sporadic PD 14 , especially in patients older than 69 years 4 . Additionally, Shi et al 15 indicated association of GSTP1 and PD when studying mice neuronal cells treated with neurotoxic substances. GSTP1*A prevented neuronal loss -contrary to GSTP1*B and GSTP1*C variants 15 .…”
mentioning
confidence: 99%
See 2 more Smart Citations